Triple‐Negative Breast Cancers: Associations Between Imaging and Pathological Findings for Triple‐Negative Tumors Compared With Hormone Receptor‐Positive/Human Epidermal Growth Factor Receptor‐2‐Negative Breast Cancers. (2nd July 2013) - Boisserie‐Lacroix, Martine; MacGrogan, Gaëtan; Debled, Marc; Ferron, Stéphane; Asad‐Syed, Maryam; McKelvie‐Sebileau, Pippa; Mathoulin‐Pélissier, Simone; Brouste, Véronique; Hurtevent‐Labrot, Gabrielle
Learning Objectives: Identify the features typical of triple‐negative breast cancers on mammography, ultrasound, and magnetic resonance imaging. Identify this aggressive subtype to accelerate diagnosis and treatment and improve outcomes. Compare typical imaging features of triple‐negative breast cancers with typical imaging features of HR+/HER‐ breast cancers. Abstract : Purpose: Triple‐negative (TN) breast cancers have high malignancy potential and are often characterized by early systemic relapse. Early detection is vital, but there are few comprehensive imaging reports. Here we describe mammography, ultrasound, and magnetic resonance imaging (MRI) findings of TN breast cancers, investigate the specific features of this subtype, and compare the characteristics of TN breast cancers with those of hormone receptor (HR)‐positive/human epidermal growth factor receptor (HER)‐2‐negative breast cancers. Materials and Methods: From July 2009 to June 2011, mammography and ultrasound findings of 210 patients with pathologically confirmed TN ( n = 105) and HR‐positive/HER‐2‐negative breast cancers ( n = 105) were retrospectively reviewed from our institutional database. Ultrasound vascularity was notified in 88 cases and elasticity scores were notified in 49 cases overall. Thirty‐five patients underwent MRI (22 TN and 13 HR‐positive/HER‐2‐negative). Mammograms, ultrasound, and MRI were reviewed according to the Breast Imaging‐Reporting and Data System (BI‐RADS) lexicon and classification. Results: TN breast cancers were more likely to show round, oval, or lobulated masses with indistinct margins on mammography than HR‐positive/HER‐2‐negative breast cancers. On ultrasound, TN tumors were more likely than HR‐positive/HER‐2‐negative breast cancers to show circumscribed or microlobulated margins and no posterior acoustic features or posterior enhancement‐positive. On MRI, TN cancers exhibited suspicious aspects more often than HR‐positive/HER‐2‐negative cancers, often with rim enhancement‐positiveHER‐2 (84.6% of masses were classified BI‐RADS 5). Conclusion: This study is the first to describe findings on mammography, ultrasound, and MRI for TN breast cancers with a matched HR‐positive/HER‐2‐negative control group. Several distinctive morphological features of these aggressive tumors are identified that can be used for earlier diagnosis and treatment, and ultimately to improve outcomes. Abstract : Early detection of triple‐negative (TN) breast cancer is vital, but there are few comprehensive imaging reports. Here we describe mammography, ultrasound, and magnetic resonance imaging findings of TN breast cancers, investigate the specific features of this subtype, and compare the characteristics of TN breast cancers with those of hormone receptor‐positive/human epidermal growth factor receptor‐negative breast cancers. Abstract : 摘要 目的 . 三阴性（ TN ）乳腺癌恶性度高，通常以早期全身复发为特征。早期检出三阴乳腺癌至关重要，但迄今还很少开展广泛的影像学研究。在本文中，我们描述了三阴性乳腺癌的乳腺摄影、超声和磁共振成像（ MRI ），探讨了这一乳腺癌亚型的特点，同时比较了三阴性乳腺癌和激素受体（HR）阳性/人表皮生长因子受体（ HER）‐2阴性乳腺癌的特征。 材料和方法： 2009年7月 ～2011年6月，对本机构数据库中的210例经病理学检查证实的三阴性乳腺癌患者（ n = 105）和 HR 阳性/HER‐2阴性乳腺癌患者（ n =105）的乳腺摄影和超声结果进行回顾性分析。总体来看，88例患者有超声血管分布结果，49例患者有弹性评分结果。35例患者接受了 MRI检查（22例三阴性乳腺癌患者，13例 HR 阳性/HER‐2阴性乳腺癌患者）。根据乳腺癌影像学报告和数据系统（ BI‐RADS ）术语和分类来评价乳腺摄影、超声和 MRI 结果。 结果： 三阴性乳腺癌较HR阳性/HER‐2阴性乳腺癌更有可能在乳腺摄影中出现圆形、卵圆形或边缘不清晰的分叶状肿块。超声检查中，三阴性乳腺癌较 HR 阳性/HER‐2阴性乳腺癌更有可能出现局限性边缘或小分叶边缘，同时无后方回声或后方增强阳性。 MRI 检查中，三阴性乳腺癌较 HR 阳性/HER‐2阴性乳腺癌更有可能出现可疑征象，常伴有边缘增强阳性（84.6%的肿块被分类为BI‐RADS 5 ）。 结论： 本研究首次以相匹配的 HR阳性/HER‐2阴性乳腺癌作为对照，描述了三阴性乳腺癌的乳腺摄影、超声和 MRI 结果。本研究发现了这一浸润性强的肿瘤几个特殊的形态学特征，可用于更早期的诊断和治疗，最终改善患者转归。